IMPLEMENTASI MANAJEMEN PERPUSTAKAAN DIGITAL DALAM MENINGKATKAN LITERASI DIGITAL SISWA - Miftahul Huda; Septuri Septuri; Nor Rochmatul Wachidah (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the implementation of digital library management in improving students’ digital literacy at MAN 2 Bandar Lampung. The focus of the research includes four aspects: the provision of digital collections, processing of digital collections, management of the digital library information system, and digital information access services. Methods: This research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation involving the head of the library, librarians, teachers, and students. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing, and validity was ensured through source and technique triangulation. Results: The implementation of digital library management at MAN 2 Bandar Lampung is carried out through the management of digital collections, information systems, and access services. The library uses the Erlangga E-Library with 960 digital books and SLiMS as its management system. This system facilitates students in independently accessing and utilizing information. The findings show that the digital library contributes to improving students’ digital literacy, particularly in accessing and utilizing digital information. Novelty: The novelty of this study lies in its examination of digital library management implementation based on management functions (planning, organizing, implementing, and controlling) in the context of a madrasah to support the enhancement of students’ digital literacy in a more comprehensive manner.